Preoperative systemic immune-inflammation index as a prognostic indicator for patients with urothelial carcinoma - Zheng, Jianxiong; Peng, Lei; Zhang, Shaohua; Liao, Haiyang; Hao, Jiayao; Wu, Song; Shen, Haili (Frontiers in Immunology, 2023)
Background The systemic immune-inflammation index (SII) is a cost-efficient indicator for carcinoma prognosis. However, its utility in urothelial carcinoma (UC) prognosis is disputed. This meta-analysis aims to assess SII’s prognostic value in UC. Methods A thorough search of databases including PubMed, Web of Science, Embase, Cochrane Library, and Scopus, was conducted to find studies until January 11, 2023. Eligibility criteria were applied to select studies. Hazard ratios (HRs) and 95% confidence intervals (CIs) were extracted from selected studies and compiled in a meta-analysis to gauge SII’s association with survival outcomes such as overall survival (OS), cancer-specific survival (CSS), recurrence-free survival (RFS), and progression-free survival (PFS). Results This analysis includes 19 studies with 12505 UC patients. It was found that high SII significantly correlated with worse OS in UC patients (HR 1.430, 95% CI 1.237-1.653, P<0.001). High SII values also linked with poorer CSS (HR 1.913, 95% CI 1.473-2.485, P<0.001), RFS (HR 1.240, 95% CI 1.097-1.403, P=0.001), and PFS (HR 1.844, 95% CI 1.488-2.284, P<0.001) compared to low SII values. Subgroup analysis revealed SII’s consistent prognostic value in UC across races, carcinoma types, sample sizes, and SII cut-off values, suggesting its potential as a prognostic indicator in UC patients. Conclusion Current evidence suggests SII as a promising, cost-efficient predictor in UC patients. This meta-analysis indicates SII’s potential as a valuable prognostic tool in UC patients. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=307643, identifier CRD42022307643.